REAKTUALISASI KONSEP IDDAH DALAM PERNIKAHAN - Hendri Kusmidi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2017)
Abstract: God has ordained the waiting period, the waiting period because there is some wisdom that is priceless and is a source of life such regularity is as if in the woman’s assertion that still contained the seeds of the fetus or not, so that later nasabnya not stir. Similarly, to give them an opportunity to refer to her husband and aware of the excesses of blindly, having thought out and considered deeply. Also the waiting period, it will be seen how the mercy of God to man, because the wait was going to find out how good a person is married or unmarried, and how unfortunately divorce so that the act was lawful but hated by Allah. The waiting period for a woman who left her husband dead, then it is a time when it appeared in mourning, so that increasingly felt tribute to her husband.